Sitting Next to a Dropout: Academic Success of Students with More Educated Peers - Daniel Goller; Andrea Diem; Stefan C. Wolter (Institute of Labor Economics (IZA), 2022)
We investigate the impact of the presence of university dropouts on the academic success of first-time students. Our identification strategy relies on quasi-random variation in the proportion of returning dropouts. The estimated average zero effect of dropouts on first- time students' success masks treatment heterogeneity and non-linearities. First, we find negative effects on the academic success of their new peers from dropouts re-enrolling in the same subject and, conversely, positive effects of dropouts changing subjects. Second, using causal machine learning methods, we find that the effects vary nonlinearly with different treatment intensities and prevailing treatment levels.
Keywords: A23; C14; I23; 330; university dropouts; peer effects; better prepared students; causal machine learning